Training Needs for Phisycal Education Teachers Who Teach in Basic Schooles - Mohamed, Ahmed Q. (Humanities Journal of University of Zakho, 2015)
An phisycal education teacher’s ability to master teaching and technical skills has become a necessity in an age of huge knowledge flow and technological development. The identification of a teacher’s training needs represents the diagnostic phase of the training process in order to determine the contex and dimensions covered by the training. This enables the teacher to perform his/her role to achieve the desired goals of teaching phisycal education. The study aims to limit the training needs of phisycal education teachers who teach at the stage of basic education in Iraqi Kurdistan, by attempting to answer the following two questions: What are the training needs of phisycal education teachers who teach students at the stage of basic education in Iraqi Kurdistan? Are there any differences in the responses of phisycal education teachers with regard to training needs, according to the variables of (gender, years of work experience,and academic qualifications)? The study relied on the descriptive approach, through the applying a questionnaire prepared for this purpose. The sample consisted of 122 male and female who were deliberately selected from phisycal education teachers of the basic education schools in the province of Duhok, Kurdistan Region of Iraq. The data contained in the search were processed using the Statistical Package of Social Sciences (SPSS). The results revealed the presence of a list of (12) training needs from the perspective of the teachers and showed that there are no significant differences in those requirements depending on the variables of gender, years of work experience, and academic qualifications . In light of the results, a set of recommendations and proposals were presented.